Creating sustainable development at Kampung Tengah, Gombak - Aung, Maulana Akbar Shah @ (IIUMTODAY, 2021)
A Day at Kampung Tangah, Gombak Special attention towards Prosperity of People called Insan Sajehtera is the most preferable and significant project of IIUM. Keeping in mind that the improving quality of faith (Iman), knowledge (Ilm) and good character (Akhlaq), we are liable to serve as agents of comprehensive progress for sustainable Development of Malaysia and Muslim Ummah. Dr Maulana, from FIDS, and Dr Lee, of PS are assigned to engage at Kampung Tengah Gombak, for implementing our project of SDG.